Hipapi Sulawesi Communication Strategy in Building a Brand of Master of Ceremony for Weddings in Makassar - Andi Muhammad Rahmat. B; Andi Vita Sukmarini; Abdul Samad (Journal Social Civilecial, 2026)
This study aims to determine the communication strategy of HIPAPI South Sulawesi in Building the Brand of Wedding Master of Ceremonies (MCs) in Makassar. This research was conducted at the Indonesian Wedding MC Association (HIPAPI) South Sulawesi. This study used a qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. This research was motivated by the increasing demand for professionalism among wedding MCs in Makassar, which is not yet fully supported by a strong image and competency standards. This study aims to analyze the communication strategies implemented by HIPAPI South Sulawesi in building the brand of wedding MCs and their implications for increasing brand awareness and professional image. The results indicate that the communication strategies implemented include the use of social media, member training, and collaboration with wedding vendors. These strategies contribute to increased brand awareness and strengthen MC's image as a competent and standardized profession. Furthermore, public trust is enhanced, impacting job opportunities and the economic value of MC services. These findings highlight the importance of a structured communication strategy in building a professional image and provide practical benefits for the development of professional organizations and service industry players.